INTERACTIVE SYSTEM FOR STUDY OF CAR'S MOVEMENT WITH LOW AND ULTRA-LOW PROFILE TIRES IN A TURN (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
In this paper an interactive system for the study of the movement of a car in a turn is proposed. The interactive system is implemented on a modular principle in the MATLAB environment. The system operates on an algorithm, taking into account the current redistribution of the vertical wheel load and its effect on the characteristics of the lateral slip of wheels with low and ultra-low profile tires. The capabilities of the interactive system are visualized with graphical dependencies.